(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Interventi legislativi della Regione Lombardia sui luoghi di culto - 2. La sentenza della Corte costituzionale n. 504 del 2019 sulla l.r. Lombardia del 2005 - 3. Pianificazione urbanistica secondaria e politiche regionali - 4. Considerazioni conclusive. The so-called "anti-mosque" legislation between governance policies and protection of religious freedom ABSTRACT: A recent intervention by the Constitutional Court of 2019 continued in the path intended to dismantle the Lombard legislation, also known as the "anti mosque" law, underlining the danger of a federalism, producing a growing fragmentation in a matter of such delicate constitutional relevance. The Court has currently canceled the obligation to regulate, through a Plan for religious equipment (PAR), the opening of any place of worship and the need to associate this Plan with the PGT (Territorial Government Plan). A territorial governance project, in fact, from the point of view of urban planning, must include the legal discipline of social religiosity, contextualising this intervention with the need for a structuring of aggregation spaces, open to all religious and secular bodies, concretely present in the social fabric. The construction of buildings intended for religious worship or, as more recently defined, of "equipment of common interest for religious purposes" is a matter by its nature suspended between the protection of religious freedom - even in its expression of collective law - and the legislation urbanism.